The mitral‐to‐aortic flow‐velocity integral ratio in the real world echocardiographic evaluation of functional mitral regurgitation before and after percutaneous repair. (3rd July 2017) - Palmiero, Giuseppe; Ascione, Luigi; Briguori, Carlo; Carlomagno, Guido; Sordelli, Chiara; Ascione, Raffaele; Pisacane, Francesca; Monda, Vittorio; Severino, Sergio; Caso, Pio
Abstract : Introduction: Percutaneous mitral valve repair (PMVR) using MitraClip system has emerged as a therapeutic option for patients with functional severe mitral regurgitation (FMR) at prohibitive risk for surgery. In this setting, the echocardiographic assessment of FMR severity is challenging because the traditional echocardiographic methods have important limitations. The aim of this study was to assess the accuracy and reliability of a simple Doppler index, the mitral/aortic flow velocity integral ratio (MAVIR), to evaluate residual FMR severity after PMVR. Methods: Eighty‐five heart failure patients with functional MR and LV dysfunction (LVEF ≤ 40%) were included. FMR was quantified on the basis of traditional quantitative parameters of MR severity. MAVIR was expressed as the ratio of mitral and aortic time velocity integral (TVI) values. According to MR severity, 25 patients underwent MC implantation and at 6 months a complete echocardiographic follow‐up was performed. Results: A significant linear relationship was found between MAVIR and both VC and EROA. A MAVIR ≥1.02 identified pts with severe MR with a sensitivity of 86.7% and a specificity of 90.9%. At the 6 months echocardiographic follow‐up after the MitraClip implantation, we observed a significant reduction of LAVI, LVED and LVES volume, while LVEF improved. Furthermore, MAVIR significantly decreased its decrease showed a significant linear relationship with LAVI reduction. Conclusion: Our data show a close relationship between MAVIR and traditional indexes of MR severity in patients with FMR. This Doppler‐derived index seems applicable after PMVR where traditional echocardiographic index of MR severity shows significant limitations.